Kajian Efektivitas Tanaman Sansevieria trifasciata dalam Mereduksi Konsentrasi Gas Carbon Monoxide (CO) di Jalan Raya Kabupaten Ponorogo - Eka Rosanti; Ratih Andhika A. R (Poltekkes Kemenkes Yogyakarta, 2017)
The Increase of the number of motor vehicles in Ponorogo Regency can diminish air quality due to the pollutant emissions from burning fuel, i.e. carbon monoxide (CO) gas. As an effort to maintain air quality, it is necessary to plant Sansevieria trifasciata, since the plant contains pregnane glycoside which is able to absorb 107 kinds of hazardous elements. The present stu-dy attempts to know the effectiveness of Sansevieria trifasciata plant in reducing the concentra-tion of CO gas in the mainroads of Ponorogo Regency. The type of the research was an analy-tical one with experimental study design. The locations of the research were at Sultan Agung Street, K. H. Ahmad Dahlan Sreet, Urip Sumoharjo Timur Street, Urip Sumoharjo Barat Street and Diponegoro Street. The planting was conducted at a distance of every two meters and the treatment was applied within two weeks.This study also measured some environmental factors, such as temperature, humidity, and wind speed to determine the homogeneity of the data. The statistical test used was paired sample t-test in order to know the difference of CO gas concen-tration between pre-treatment and post-treatment. The results show that CO gas concentrations before and after planting Sansevieria trifasciata were significantly different (p-value = 0,009).